Cultivating Early-Age Independence in Indonesian Islamic Boarding Schools: A Case Study from Pesantren Mambaul Hisan - Lailatu Rohmah; Edi Purwanta; Sugito Sugito (Jurnal Ilmiah Peuradeun, 2026)
The development of independence among early-age Santri in Indonesian Islamic boarding schools presents a unique educational challenge due to their young age and reliance on adult supervision. This study investigated how structured pedagogical strategies—modeling, mentoring, and motivation—were employed to cultivate independence among 5- to 6-year-old students at Pesantren Mambaul Hisan (Mamhis). Using a qualitative case study design with interviews and field observations, the research revealed a systematic transition to self-reliance facilitated by three core strategies: direct exemplification, guided assistance, and motivational reinforcement. The novelty of this study resided in its exploration of these strategies within the context of residential Islamic education, a domain that was infrequently examined in early childhood research. The findings showed that age-based admission policies, combined with consistent scaffolding, gradually empower Santri to manage daily responsibilities while aligning with religious and cultural values. Theoretically, the study extends ecological systems and self-determination perspectives into pesantren education. Practically, it offers information to policy makers and educators in designing caretaker training and integrating independence building into character education. Despite its limited scope, this study highlights pesantren as a culturally grounded model for fostering early independence and calls for comparative and longitudinal research to broaden understanding.